2000
DOI: 10.1046/j.1460-9568.2000.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐1 is a marker for a subpopulation of putative nociceptive neurons in rat dorsal root ganglia

Abstract: Immunocytochemical and morphometric techniques were used to quantify the distribution of cyclooxygenase (cox)-containing neurons in rat L5 dorsal root ganglia (DRG). Cox-1 immunolabelling was almost exclusively restricted to small diameter DRG neurons (< 1000 microm2), and was extensively colocalized with calcitonin gene-related peptide (CGRP) and isolectin B4 (IB4). Cox-1 was present in 65% and 70% of CGRP- and IB4-labelled neurons, respectively. Cox-1 labelling was also found in neurons expressing the sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 50 publications
(121 reference statements)
1
39
2
Order By: Relevance
“…Furthermore, the analgesic effects of these drugs often occur at significantly lower doses than those needed to inhibit inflammation (22). Clinical and experimental association of COX-1 and pain may be functionally explained by the finding that COX-1 is a marker for subpopulations of putative nociceptor neurons in the dorsal root ganglion (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the analgesic effects of these drugs often occur at significantly lower doses than those needed to inhibit inflammation (22). Clinical and experimental association of COX-1 and pain may be functionally explained by the finding that COX-1 is a marker for subpopulations of putative nociceptor neurons in the dorsal root ganglion (23).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the levels of COX-3 mRNA in human and canine cerebral cortex are relatively low. This may be due to cell type-specific expression such as has been shown for COX-1 immunoreactive protein in a subpopulation of putative nociceptor neurons (23). However, COX-3 in human will require further experimentation because some of the published sequences differ by one nucleotide in intron 1 and hence are out of frame.…”
Section: Discussionmentioning
confidence: 99%
“…Further morphological study showed that increased COX2 in Vc was expressed only by neurons, and most of these COX2-immunoreactive neurons were activated. With regard to COX2 expression in sensory ganglia, Chopra et al (2000) showed that COX2 was not induced in dorsal root ganglion in the Freund's adjuvant model of monoarthritis, but a recent study exhibited that intraplantar injection of carrageenan could elicit COX2 expression in dorsal root ganglion (Pham-Marcou et al, 2008). In the present study, no COX2 expression was observed in trigeminal ganglion neurons after rubber band insertion (data not shown), which further supported our viewpoint that it was COX2 induction in Vc that generated orofacial nociception during tooth movement.…”
Section: Cox2 and Orthodontic Painmentioning
confidence: 99%
“…COX-1 and COX-2 are both constitutively expressed in neural tissue (30,50). COX-1 is traditionally characterized as a ''housekeeping'' enzyme in homeostatic production of prostaglandins for activities that include maintenance of glycerophospholipid levels and membrane remodeling (37,103).…”
Section: Cyclooxygenasementioning
confidence: 99%